ANALISIS PENGARUH ASET PAJAK TANGGUHAN, ASIMETRI INFORMASI, DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2010-2012 - Stella Mettawidya; Hardi -; Edfan Darlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research is to analyze of deferred tax assets, information asymmetry, and firm size effect on earnings management in LQ45 companies listed in Indonesia Stock Exchange 2010-2012. Independent variables used in this research is the deferred tax assets, information asymmetry, and firm size, while the dependent variables used in this research is earnings management. The research sample in this research consisted of 18 companies listed in LQ45 Indonesia Stock Exchange in the period 2010-2012, which were selected based on specific criteria by using purposive sampling method. Analysis of the data used in this research is multiple regression analysis were processed using SPSS version 17. The results of the conducted research simultaneously shows, deferred tax assets, information asymmetry and firm size has a significant influence on earnings management with value of Fhit> Ftable (5.034> 2.790). In contrast, the partial test results show that the: (1) the deferred tax assets do not have a significant effect on earnings management with a significant level or pvalue of 0.061, (2) information asymmetry significant effect on earnings management with a significant level or pvalue of 0.043, and (3 ) firm size have a significant effect on earnings management with a significant level or pvalue of 0.001.Keywords: earnings management, deffered tax asset, information asymmetry, and firm size.